Mapping Schools’ Strength in Inclusive Education Learning for Building Language Competence in Wetland Ecological Awareness - Moh Yamin; Utomo Utomo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This research aims at mapping schools’ strength in facilitating the inclusive education learning towards for building language competence in wetland ecological awareness. It is descriptive in qualitative approach. The respondent is teachers in three schools, namely state junior high school 13, 15, and 21 in Banjarmasin. The instrument used is questionaire and interview. The results state that there has been positive teachers’ perception about inclusive education dealing the adaptation of the curriculum and/or individual learning plans, teaching and learning materials for learners with special needs, communication skill in accordance with the characteristics of children with special needs, and the minimum completeness criteria for children with special needs that are in accordance with their abilities and needs. There is also positive perception about Banjarmasin as the peat area, loving the river as the manifestation of taking care of the river, and the ecological education to maintain and keep Banjarmasin as a city of a thousand rivers inserted in certain subject. However, in practice, all teachers do the task based on limited knowledge and experience. Strengthening language competence so that the teacher can interact wih the learners for special needs inspite of limited knowledge and experience should be conducted.